The Impact of Fiscal Consolidations on Growth in Sub-Saharan Africa - Arizala, Francisco; Gonzalez-Garcia, Jesus; Tsangarides, Charalambos; Yenice, Mustafa (Washington, D.C. : International Monetary Fund, 2017)
This paper examines the output effects of changes in public expenditure and revenue in sub-Saharan African countries during 1990-2016. Fiscal multipliers in sub-Saharan Africa are somewhat smaller than those in advanced and emerging economies. The effect of changes in fiscal policy on output depends on the composition: cutting public investment has a larger effect on output than cutting public consumption or raising revenue. Episodes of fiscal consolidation have short- and medium-term output effects, but here, too, composition matters: fiscal consolidations based on reducing public investment have the largest effect on output, while fiscal consolidations based on revenue mobilization are less harmful than those based on public investment cuts. These findings suggest that the negative impact on growth can be mitigated through the design of fiscal adjustment and the accompanying policy environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet